2023
DOI: 10.1007/s12672-023-00701-7
|View full text |Cite
|
Sign up to set email alerts
|

Possible therapeutic targets for NLRP3 inflammasome-induced breast cancer

Abstract: Inflammation plays a major role in the development and progression of breast cancer(BC). Proliferation, invasion, angiogenesis, and metastasis are all linked to inflammation and tumorigenesis. Furthermore, tumor microenvironment (TME) inflammation-mediated cytokine releases play a critical role in these processes. By recruiting caspase-1 through an adaptor apoptosis-related spot protein, inflammatory caspases are activated by the triggering of pattern recognition receptors on the surface of immune cells. Toll-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 137 publications
0
6
0
Order By: Relevance
“…BC represents a growing global concern, especially for the female population of working age. Its pathophysiology presents a series of challenges, including the need to identify new prevention and treatment strategies, aiming to improve patients’ quality of life affected by this disease [ 46 , 47 , 48 , 49 ]. Recent studies have provided promising evidence of the benefits of omega-3 supplementation and complementary therapies in combination with chemotherapy, radiotherapy, and surgical procedures for patients with BC [ 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…BC represents a growing global concern, especially for the female population of working age. Its pathophysiology presents a series of challenges, including the need to identify new prevention and treatment strategies, aiming to improve patients’ quality of life affected by this disease [ 46 , 47 , 48 , 49 ]. Recent studies have provided promising evidence of the benefits of omega-3 supplementation and complementary therapies in combination with chemotherapy, radiotherapy, and surgical procedures for patients with BC [ 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dexamethasone-loaded ROS-responsive polymer nanoparticles prepared by a modified emulsion approach had a strong ability to inhibit the expression of NLRP3, caspase1, and IL-1 [204]. It has been reported that nanoparticles themself trigger NLRP3 inflammasome activation [205][206][207][208]. However, the formation of a protein corona layer on lipid NPs caused a significant reduction in NLRP3 inflammasome activation and controlled the toxicity, biodistribution, and cellular uptake [209].…”
Section: Nlrp3 Inflammasome Inhibitors and Their Limitations As Remed...mentioning
confidence: 99%
“…Moreover, dexamethasone-loaded ROS-responsive polymer nanoparticles prepared by a modified emulsion approach had a strongest ability to inhibit the expression of NLRP3, caspase1, and IL-1b [207]. It has been reported that nanoparticles itself trigger the NLRP3 inflammasome activation [208][209][210][211]. However, the formation of protein corona layer on lipid NPs caused a significant reduction in NLRP3 inflammasome activation and controls the toxicity, biodistribution, and cellular uptake [212].…”
Section: Nlrp3 Inflammasome Inhibitors and Their Limitations As Remed...mentioning
confidence: 99%